The platform economy and the precarisation of food delivery work in the COVID-19 pandemic: Evidence from India. (1st January 2021) - Parwez, Sazzad; Ranjan, Rajiv
Abstract : This study aims to explore work precarity in the platform economy from the perspective of food delivery workers. It also tries to contextualise work precarity in COVID-19 times. With the digital boom, food-based platform aggregators have emerged as a new workspace for food delivery workers in India. Food delivery workers working for platform aggregators are termed 'independent contractors' and 'delivery partners' to avoid legal issues of employer-employee relations; this enables a substantial reduction in transaction costs. Despite the huge number of food delivery workers, they are unable to organise into collectives. The platform economy is emerging as a sector offering new work opportunities, but at the same time it is plagued by low wages (and benefit), absence (or lack) of welfare measures, and digital controls contributing to the process of precarisation. The COVID-19 pandemic and resultant lockdown have aggravated the precarity of work for food delivery workers. It has led to the loss of jobs and incomes, and increased health risks, stigmas and occupation distress. Further, autonomy and flexibility should not come at the cost of the most basic social security and protection. This precarious situation calls for affirmative action from policymakers and platform aggregators.